Educating teachers and tomorrow's students through service-learning pedagogy - Jagla, Virginia M., 1948-; Tice, Kathleen C. (Advances in service-learning research., 2019)
"Service-learning is a powerful method of teaching and learning that has been used effectively for more than two decades. This volume contributes further to the Advances in Service-Learning Research series that focuses upon service-learning in teacher education. Research and theory indicate that knowledge of service-learning pedagogy and how to implement it in teacher candidates' future classrooms can enhance field experiences of teacher education and the civic mission of schools. However, research also reminds us that that the practice of service-learning is nuanced and complex. No two service-learning experiences are alike, yet universal characteristics across service-learning experiences define its essence and distinction. It is through research that digs deep into these nuanced issues that we can learn more about the different characteristics of the experience that define service-learning and guide implementation. The preface provides an interview with Andy Furco, an early advocate of service-learning and noted leader who has fostered service-learning in K-12 and higher education throughout the United States and across the globe. Andy Furco's commentary offers an historical overview of the field as well as how the field can advance, providing insights for those new to the field as well as those who have engaged in service-learning. The preface and thirteen chapters together provide empirical and conceptual support for including service-learning. Concurrently, this scholarship provides guidance for implementing service-learning in teacher preparation and in K-12 education. Interrelated themes include self efficacy, connections with communities, diversity, and program development in teacher education" --